User Satisfaction level of Self-lending Machine using the End User Computing Satisfaction (EUCS) Model at the National Library of the Republic of Indonesia - Fitri Aulia; Gustina Erlianti (Universitas Pancasakti, 2026)
Libraries have undergone a significant transfomation from manual systems to automated services as part of advances in information technology. One innovation in circulation services is the implementation of self-lending machines to improve efficiency and user independece. This study aims to evaluate the utilization of self-lending machines at the National Library of the Republic on Indonesia using the End User Computing Satisfaction (EUCS) model, which includes ontent, accuracy, format, ease of use, and timeliness. This research employes a quantitative approach with a descriptive method. Data were collected through quastionnaires distributed to 86 respondents selected using purposive sampling. The results show that overall user satisfaction is categorized as ver satisfied. The content and accuracy dimensiones obtained the highest mean scores, followed by format and ease of use, while timeliness recorded the lowest score. These findings indicate that the system has been effectively implemented and is able to meet user needs, altough improvements are still required in terms of system responsiveness and usability. This study highlights the importance of continuous evaluation to enchance technology-based library services and improve user-oriented service quality.